Survival of E. coli O157:H7 on hydroponically grown traditional and microgreen Genovese and Lemon basil (Ocimum basilicum) under home-scale conditions - Espinoza A., Gleydi L. (Zamorano: Escuela Agrícola Panamericana, 2025)
The consumption of fresh culinary herbs, especially basil, has increased due to their health benefits. Consequently, their production has surged, particularly in hydroponic systems at home. Since culinary herbs are often consumed raw, they pose a food safety risk if contaminated. Recent outbreaks in hydroponic production have shown that foodborne pathogens can survive in these systems, including components such as nutrient solutions, growth mats, and roots. For this reason, this study determined the survival rates of E. coli O157:H7 within hydroponic units of Genovese and Lemon basil cultivars under home-scale conditions. The study compared the survival of E. coli O157:H7 over 27 days and 14 days in the traditional and microgreen systems, respectively. Bacterial counts were monitored in the nutrient solution, growth mat, and root samples to evaluate each variety's microbial interactions and possible inhibitory effects. Results indicated a significant reduction in bacterial counts over time (p < 0.05). In the traditional system, E. coli O157:H7 decreased from 6 Log CFU/mL to 0 Log CFU/mL over 27 days, while in the microgreens system, it reduced from 5 Log CFU/mL to 1 Log CFU/mL over 14 days. No significant differences were observed between the two basil varieties within each system (p > 0.05). Both varieties showed similar bacterial reduction in all samples, suggesting that bacterial persistence may depend more on factors other than variety influence in bacterial survival. These findings highlight the potential of growing basil in traditional and microgreen systems to mitigate bacterial contamination, with implications for ensuring food safety and improving agricultural practices.